2022
DOI: 10.26459/hueunijard.v130i3c.6571
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Characteristics of Ehrlichia Canis Infection in Dogs in Thua Thien Hue

Abstract: The survey was carried out at OKADA PET Veterinary Center, Hue City, with 935 dogs                             of different ages and breeds. The results show that 39.6% of dogs have the clinical signs of Ehrlichia canis     (E. canis) infection, 95.7% of which were serologically positive for E. canis antibody. The results also indicate that 54.9% of dogs have E. canis morulae in monocytes and/or neutrophils. Statistical analysis reveals that the prevalence of E. canis infection in dogs is not affected by breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Consequently, it was also known as 'tracker dog disease' and 'tropical canine pancytopenia' . The infection was then discovered in other locations around the world, including the United States, countries in South America, Africa, and Asia (Hai, Khuong, 2021). The infection primarily affects the leukocytes (monocytes, macrophages, and neutrophils) of the mammals as well as the salivary gland, the gut, and hemocoel cells of tick.…”
Section: Ehrlichiosismentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, it was also known as 'tracker dog disease' and 'tropical canine pancytopenia' . The infection was then discovered in other locations around the world, including the United States, countries in South America, Africa, and Asia (Hai, Khuong, 2021). The infection primarily affects the leukocytes (monocytes, macrophages, and neutrophils) of the mammals as well as the salivary gland, the gut, and hemocoel cells of tick.…”
Section: Ehrlichiosismentioning
confidence: 99%
“…All dog breeds can contract E. canis, but German shepherds seem to be more vulnerable because this breed exhibits more severe form of the disease and has a greater morbidity and mortality rate compared other breeds (Harrus, Waner, 2011). In other studies, it was demonstrated that the risk of E. canis infection does not depend on the breed (Hai, Khuong, 2021). Due to the several phases and numerous clinical presentations of the disease, diagnosis can be difficult.…”
Section: Ehrlichiosismentioning
confidence: 99%
See 2 more Smart Citations
“…The following make up each 100 g edible portion of okra pods: Ca 84 mg, P 90 mg, Fe 1.2 mg, water 88.6 g, energy 144 kJ (36 kcal), protein 2.1 g, carbohydrate 8.2 g, fat 0.2 g, fibre 1.7 g, ascorbic acid 47 mg, thiamin 0.04 mg, riboflavin 0.08 mg, niacin 0.6 mg, and β-carotene 185 μg (Sorapong, 2012). The young immature okra pod is consumed as a nutritious dish in a variety of ways (fresh, boiling, dried, or fried), and the seed is used to make oil (Hai & Thao, 2022). The fruits are picked and eaten like vegetables when they are immature (Singh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%